Steel design - Segui, William T. (Cengage Learning, 2013)
Covers the fundamentals of structural steel design with an emphasis on the design of members and their connections, rather than the integrated design of buildings. This book encourages the application of fundamental principles for design procedures as well as for practical design, and provides a theoretical approach to enhance student development.